ENT 530 : Case Study: Fleurishbaby / Nabiha Ali Redza ... [et al.] - Ali Redza, Nabiha; Ali Redza, Nadia; Anuar, Wan Amelia Syahirah; Mohamed Hanapi, Hanis Hazirah; Mohamad, Rasyidah (2021)
The case study is focused on the ability of a small business, Fleurishbaby to sustain the business as it will affect their company cash flow and economy growth as the demand on bouquets will be lower. The strength of small businesses depends on how business owner strategized to perform her duties to save the company. During the Covid-19 pandemic, all small business owner struggling to survive in the industry where the business is in. Further analysing the business’ opportunities and threats. There are several problems that occurred in the Fleurishbaby Business, but this case study is about selling the products that is not an essential based product. Meaning that the product will less likely be on demand on daily but on certain occasions. Focusing on identify one major problem and solutions to help the business owner in facing the industry reality. The findings of case study are based on the online interview that have been carried out with the business owner to get the facts about her small business. Therefore, the case study for Fleurishbaby business is to measure the sustainability of the business owner in facing the problem and the capability to survive within this pandemic and challenges. This case study summarises the impact towards small businesses and ways on supporting small and medium-sized enterprises in Malaysia.